Photoresist composition based on metal nanoparticles and application thereof

By using a photoresist composition containing metal nanoparticles, combined with ultraviolet, extreme ultraviolet, or electron beam exposure techniques, the challenges of complex photoresist processes and high-resolution patterning have been solved, enabling high-resolution photolithographic patterning and direct construction of conductive patterns, suitable for the fabrication of micro and nano devices.

CN121325510APending Publication Date: 2026-01-13TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511552091.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2020-08-03
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing photoresist processes are complex and prone to errors during pattern transfer, making it difficult to meet the processing requirements of high-resolution devices. Furthermore, traditional inkjet printing methods are insufficient for patterning high-resolution metal nanomaterials.

Method used

A photoresist composition comprising metal nanoparticles, photosensitizers, anti-diffusion agents, and photoresist solvents is used to form a photoresist coating by spin coating. Micro-nano patterns are then formed using ultraviolet, extreme ultraviolet, or electron beam exposure techniques, followed by heat treatment to achieve conductive patterning.

Benefits of technology

High-resolution photolithographic patterning was achieved, simplifying the process flow and reducing pattern transfer errors. Furthermore, the metal nanoparticle photoresist has excellent conductivity, making it suitable for the fabrication of micro and nano devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121325510A_ABST
    Figure CN121325510A_ABST
Patent Text Reader

Abstract

The invention discloses a photoresist composition based on metal nanoparticles and application of the photoresist composition. The photoresist composition comprises metal nanoparticles, a photosensitizer, an anti-diffusion agent and a photoresist solvent, wherein the metal nanoparticles are silver nanoparticles, copper nanoparticles and gold nanoparticles. The photoresist composition has good film-forming property and excellent patterning imaging capability, photoetching patterns with different resolutions can be obtained through ultraviolet, electron beam or extreme ultraviolet exposure, and the formed patterns have good conductivity after being subjected to heat treatment and can be directly used for processing micro-nano devices.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent entitled "Photoresist Composition Based on Metal Nanoparticles and Its Application", application number 2020107694555, with the parent application date being August 3, 2020. Technical Field

[0002] This invention belongs to the field of materials technology, specifically relating to a type of photoresist composition based on metal nanoparticles and its applications. Background Technology

[0003] Photoresist is one of the most important core materials in photolithography, widely used in the microfabrication of integrated circuits and discrete semiconductor devices. By coating photoresist onto the surface of a semiconductor, conductor, or insulator, the remaining portion after exposure and development protects the underlying substrate. Etching then transfers the desired micro-pattern from the photomask to the substrate. Traditional photoresist materials use organic materials such as polymers or monomeric resins. These organic photoresists have excellent film-forming properties and are easy to process. As the medium for pattern processing in photolithography, photoresist provides etch resistance or stripping protection for subsequent pattern transfer, enabling pattern transfer. However, this pattern transfer process requires sophisticated equipment and materials, is relatively complex, and inevitably introduces errors during the transfer process, posing challenges to device fabrication.

[0004] In recent years, a class of organic / inorganic hybrid photoresist materials has been developed. These photoresists can directly fabricate metal or oxide patterns of conductors or semiconductors at the micro- and nano-scale using deep ultraviolet (DUV), electron beam, and even extreme ultraviolet (EUV) lithography techniques, attracting widespread attention. By selecting and designing materials, the photoresist can be functionalized, becoming an integral part of the device after exposure and development, participating in the device's functional construction without the need for subsequent etching and stripping pattern transfer processes. This one-step pattern formation method greatly simplifies the process flow and minimizes errors during pattern transfer. For example, Lin et al. used an indium gallium zinc oxide (IGZO) precursor solution as a deep ultraviolet (DUV) photoresist and successfully fabricated semiconductor IGZO trenches in thin-film transistors (TFTs) using DUV laser direct writing technology. Scientific Reports Yeh et al. used zinc methacrylate as a deep ultraviolet negative photoresist material to directly obtain ZnO nanostructures with a size of less than 300 nm under DUV lithography, which is expected to be used for the fabrication of ZnO semiconductor devices. Advanced Materials Interfaces, 2016, 3 1600373 )。The patterning technology of direct-write photolithography using inorganic nanomaterials has made it possible to develop and functionalize novel photoresist materials, and has good application prospects.

[0005] Some special metallic nanoparticles, such as gold, silver, and copper nanoparticles, possess unique physicochemical properties, including high electrical and thermal conductivity, surface-enhanced Raman scattering, chemical stability, catalytic activity, and high antibacterial activity. These properties make them potentially valuable in inks, microelectronics, and medical imaging. Silver and copper nanomaterials are among the most widely used nanomaterials in commercial products, especially in the fabrication of microcircuits. Silver and copper nanoparticles can be used as conductive inks, achieving patterning and conductivity of metallic silver or copper nanoparticle inks through inkjet printing and low-temperature sintering. Int. J. Mol. Sci. , 2019, 20 , 2124; Applied Materials & Interfaces , 2014, 6 (768) Although this inkjet printing method is simple to operate, it is mainly for low-resolution devices and is difficult to implement for devices with high resolution requirements. Summary of the Invention

[0006] The purpose of this invention is to provide a photoresist composition comprising metal nanoparticles.

[0007] This invention is achieved through the following technical solution: A photoresist composition comprising metal nanoparticles, a photosensitizer, an anti-diffusion agent, and a photoresist solvent, wherein the metal nanoparticles are silver nanoparticles, copper nanoparticles, or gold nanoparticles.

[0008] According to the present invention, the particle size of the metal nanoparticles in the photoresist composition is preferably 1-50 nm.

[0009] According to the present invention, the surface of the metal nanoparticles has an organic stabilizer, such as C. 8-30 Saturated or unsaturated fatty acids, C 8-30 One or a mixture of two or more saturated or unsaturated fatty amines. For example, the stabilizer may be oleic acid, oleylamine, or a mixture of oleic acid and oleylamine. The metal nanoparticles may be soluble in a photoresist solvent. According to the present invention, the inorganic components contained in the metal nanoparticles are 60%-95% by mass, preferably 80%-93%.

[0010] According to the present invention, the metal nanoparticles can be obtained by high-temperature pyrolysis of metal salts (e.g., silver salts, copper salts, gold salts). The high-temperature pyrolysis reaction temperature is, for example, 100-300°C, and the reaction time is, for example, 0.1-4 hours. For example, silver nanoparticles are obtained by high-temperature pyrolysis of silver salts in the presence of a stabilizer. The silver salt is silver acetate or silver nitrate, and the stabilizer can be C... 8-30 Saturated or unsaturated fatty acids, C 8-30 The stabilizer is a mixture of one or more saturated or unsaturated fatty amines. For example, the stabilizer may be a mixture of oleic acid and oleylamine, with a molar ratio of oleic acid to oleylamine ranging from 5:1 to 1:5.

[0011] According to the present invention, in the photoresist composition, the photosensitizer is selected from at least one of benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, diphenyl ethyl ketone, α,α-dimethoxy-α-phenyl acetophenone, α,α-diethoxyacetophenone, hydroxymethyl phenyl ketone, α-hydroxyethyl phenyl ketone, aminomethyl phenyl ketone, α-aminoethyl phenyl ketone, benzophenone, 2,4-dihydroxybenzophenone, michalcone, 2-chlorothioxanthonone, and 2-isopropylthioxanthonone.

[0012] According to the present invention, in the photoresist composition, the anti-diffusion agent is selected from C 5-20 Saturated fatty alcohols, such as saturated straight-chain C60 alcohols. 5-16 At least one of fatty alcohols, isoamyl alcohol, 2,3-dimethyl-2-butanol, and 2,3,3-trimethyl-2-butanol.

[0013] According to the present invention, in the photoresist composition, the photoresist solvent is an organic solvent selected from chlorobenzene, toluene, xylene, mesitylene, C 5-20 Alkane solvents, C 5-20 One or more of the cycloalkane solvents.

[0014] According to the present invention, in the photoresist composition, the metal nanoparticles account for 1 to 30 wt% of the total mass of the photoresist composition, preferably 1 to 20%; the photosensitizer accounts for 0.01 to 3 wt% of the total mass, preferably 0.01 to 2 wt%; the anti-diffusion agent accounts for 0.001% to 0.2 wt% of the total mass, preferably 0.001% to 0.1 wt%; and the remainder is solvent.

[0015] The present invention also provides a photoresist pattern, which is obtained by forming a coating of photoresist composition and then exposing it.

[0016] The present invention also provides a method for preparing a photoresist pattern, comprising applying the photoresist composition onto a substrate to obtain a photoresist coating, wherein the photoresist coating is exposed to obtain different patterns.

[0017] According to the present invention, the application method is spin coating.

[0018] According to the present invention, the photoresist coating is a thin film.

[0019] According to the present invention, the exposure method includes ultraviolet exposure, extreme ultraviolet exposure, electron beam exposure, etc.

[0020] Furthermore, the present invention also provides the application of the photoresist composition for the fabrication of micro / nano devices.

[0021] The photoresist is patterned and then heat-treated to exhibit good electrical conductivity, making it suitable for direct fabrication of micro and nano devices.

[0022] The beneficial effects of this invention are as follows: (1) This invention provides a photoresist composition containing metal nanoparticles, which can form a photoresist coating. Through exposure, such as ultraviolet exposure or electron beam exposure, micron- and nano-scale photolithographic patterns can be obtained. The pattern formed by the exposure of the photoresist composition film has good conductivity after heat treatment and can participate in the functional construction of devices. This invention greatly expands the application range of metal nanomaterials.

[0023] (2) The metal nanoparticle photoresist in this invention is applicable to a variety of photolithography methods. Ultraviolet exposure can achieve a resolution of 2 micrometers, and electron beam exposure can achieve a resolution of 130nm, which can well meet the resolution requirements of different types of microcircuits or devices.

[0024] (3) The method for preparing metal nanoparticles by high-temperature pyrolysis in this invention is simple to operate, has few steps, short reaction time, and controllable particle size. Attached Figure Description

[0025] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0026] Figure 1 This is a dynamic light scattering particle size distribution diagram of silver nanoparticles in Example 1 of the present invention.

[0027] Figure 2 This is a thermogravimetric curve of silver nanoparticles in Example 1 of the present invention.

[0028] Figure 3 This is a scanning electron microscope (SEM) image of the L-shaped pattern obtained by photoresist exposure at 254nm in Embodiment 2 of the present invention.

[0029] Figure 4 This is a scanning electron microscope (SEM) image of the ring pattern obtained by photoresist exposure at 254nm in Embodiment 2 of the present invention.

[0030] Figure 5 This is a scanning electron microscope (SEM) image of the stripe pattern obtained by electron beam exposure of the negative photoresist in Embodiment 3 of the present invention.

[0031] Figure 6 This is a scanning electron microscope (SEM) image of the stripe pattern obtained by exposing the negative photoresist at 13.5 nm in Example 4 of the present invention. Detailed Implementation

[0032] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments and accompanying drawings, further clarifies the invention. Those skilled in the art should understand that the specific description below is illustrative rather than restrictive and should not be construed as limiting the scope of protection of the present invention.

[0033] Example 1 Preparation method of silver nanoparticles: 560 mg of oleic acid and 530 mg of oleylamine were dissolved in diphenyl ether. Under the conditions of 80℃ oil bath temperature and N2 protection, 330 mg of silver acetate was added, and the mixture was stirred for 10 min, then heated to 160℃. After continuing the reaction for 1 h, heating was stopped, and the mixture was cooled to room temperature. The product was precipitated with ethanol. Centrifugation yielded a black precipitate, which was ultrasonically washed twice with ethanol, filtered, and vacuum dried to obtain a brown solid. Dynamic light scattering analysis showed that the prepared nanoparticles had a particle size of less than 10 nm and a distribution coefficient (PDI) of 0.216, indicating a uniform particle size distribution. Figure 1 Thermogravimetric analysis showed that the silver nanoparticles contained approximately 90% inorganic components. Figure 2 ).

[0034] Example 2 A negative photoresist formulation and ultraviolet lithography: The silver nanoparticles obtained in Example 1 were dissolved in chlorobenzene to prepare a 6% (w / w) solution. 0.03% dimethyl benzoate was added as a photosensitizer, and 0.002% isoamyl alcohol was added as an anti-diffusion agent. The solution was filtered through a 0.22 μm microporous filter to obtain the photoresist solution. This solution was then spin-coated onto an acid-base treated silicon substrate and baked at 100°C for 3 minutes. The resulting film was then exposed to 254 nm ultraviolet light. Scanning electron microscopy (SEM) revealed that the silver nanoparticle photoresist exhibited excellent patterning ability, forming L-shaped patterns with right angles (…). Figure 3No deformation occurred, demonstrating excellent patterning imaging performance; the annular pattern had high edge contrast and was completely consistent with the mask pattern, resulting in a pattern resolution of up to 2.3 μm. Figure 4 ).

[0035] Example 3 A negative photoresist formulation and electron beam lithography: Silver nanoparticles obtained in Example 1 were dissolved in xylene to prepare a 10% (w / w) solution. 0.1% α-hydroxyethylphenyl ketone was added as a photosensitizer, and 0.005% 2,3-dimethyl-2-butanol was added as an anti-diffusion agent. The solution was filtered through a 0.22 μm microporous filter to obtain a photoresist solution. This solution was then spin-coated onto an acid-base treated silicon substrate. After baking at 100°C for 3 minutes, the resulting film was exposed using an electron beam lithography machine to obtain a lithographic pattern with a period of 300 nm and a stripe width of 130 nm. (See...) Figure 5 It has high-resolution imaging capabilities.

[0036] Example 4 A negative photoresist formulation and extreme ultraviolet lithography: Silver nanoparticles obtained in Example 1 were dissolved in cyclooctane to prepare a 2% (w / w) solution. 0.02% α,α-dimethoxy-α-phenylacetophenone was added as a photosensitizer, and 0.001% 2,3,3-trimethyl-2-butanol was added as an anti-diffusion agent. The solution was filtered through a 0.22 μm microporous filter to obtain a photoresist solution. This solution was spin-coated onto an acid-base treated silicon substrate and baked at 100°C for 3 minutes. The resulting film was then exposed at the soft X-ray interferometry lithography line station (BL08U1B) of the Shanghai Synchrotron Radiation Facility (exposure wavelength 13.5 nm) with an exposure pattern period of 137 nm, resulting in very uniform photoresist stripes. (See...) Figure 6 The lithographic stripe width is 49nm, providing good resolution.

[0037] Example 5 Conductivity test: The photoresist obtained in Example 2 was spin-coated to obtain a photoresist film with a thickness of approximately 100 nm. The film was heated at 150°C for 3 minutes, and the conductivity of the film was measured to be between 1.8 and 3.6 × 10⁻⁶. 4 S cm -1 Within the specified range, the photoresist film was confirmed to have good conductivity. After heat treatment at 150 degrees Celsius on the L-shaped pattern obtained in Example 2, the conductivity test result reached 1.2 × 10⁻⁶. 4 S cm -1 It also exhibits good electrical conductivity.

[0038] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A photoresist composition based on metal nanoparticles, comprising metal nanoparticles, a photosensitizer, an anti-diffusion agent, and a photoresist solvent, wherein the metal nanoparticles are silver nanoparticles, copper nanoparticles, or gold nanoparticles.

2. The photoresist composition according to claim 1, characterized in that, The particle size of the metal nanoparticles is 1-50 nm.

3. The photoresist composition according to claim 1 or 2, characterized in that, The surface of the metal nanoparticles has an organic stabilizer, such as C. 8-30 Saturated or unsaturated fatty acids, C 8-30 The stabilizer is one or a mixture of two or more saturated or unsaturated fatty amines; for example, the stabilizer may be oleic acid, oleylamine, or a mixture of oleic acid and oleylamine. Preferably, the inorganic components contained in the metal nanoparticles account for 60%-95% by mass, more preferably 80%-93%.

4. The photoresist composition according to any one of claims 1-3, characterized in that, The metal nanoparticles are prepared by high-temperature pyrolysis of metal salts; preferably, the temperature of the high-temperature pyrolysis reaction is 100-300℃. Preferably, silver nanoparticles are obtained by high-temperature pyrolysis of silver salt in the presence of a stabilizer. The silver salt is silver acetate or silver nitrate; the stabilizer can be C... 8-30 Saturated or unsaturated fatty acids, C 8-30 A mixture of one or more saturated or unsaturated fatty amines, preferably a mixture of oleic acid and oleylamine, wherein the molar ratio of oleic acid and oleylamine is, for example, 5:1 to 1:

5.

5. The photoresist composition according to any one of claims 1-4, characterized in that, The photosensitizer is selected from at least one of benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, diphenyl ethyl ketone, α,α-dimethoxy-α-phenyl acetophenone, α,α-diethoxyacetophenone, hydroxymethyl phenyl ketone, α-hydroxyethyl phenyl ketone, aminomethyl phenyl ketone, α-aminoethyl phenyl ketone, benzophenone, 2,4-dihydroxybenzophenone, michidone, 2-chlorothioxanthonone, and 2-isopropylthioxanthonone.

6. The photoresist composition according to any one of claims 1-5, characterized in that, The anti-diffusion agent is selected from C. 5-20 Saturated fatty alcohols, such as saturated straight-chain C60 alcohols. 5-16 At least one of fatty alcohols, isoamyl alcohol, 2,3-dimethyl-2-butanol, and 2,3,3-trimethyl-2-butanol.

7. The photoresist composition according to any one of claims 1-6, characterized in that, The photoresist solvent is an organic solvent selected from chlorobenzene, toluene, xylene, mesitylene, and C. 5-20 Alkane solvents, C 5-20 One or more of the cycloalkane solvents.

8. A photoresist pattern obtained by forming a coating from the photoresist composition according to any one of claims 1-7 and then exposing it; preferably, the exposure method includes ultraviolet exposure, extreme ultraviolet exposure, electron beam exposure, etc.

9. The method for preparing a photoresist pattern according to claim 8, comprising applying the photoresist composition according to any one of claims 1-7 onto a substrate to obtain a photoresist coating, wherein the photoresist coating is exposed to obtain different patterns; preferably, the application method is spin coating.

10. The use of the photoresist composition according to any one of claims 1-7 in the fabrication of micro / nano devices.